Vascular reactivity in cerebral amyloid angiopathy - Smith, Eric E. (Henry Stewart Talks, 2023)
Effects of CAA on the vessel wall, Animal studies of cerebrovascular reactivity (CVR) in CAA, Human studies of CVR in CAA, Clinical correlates of loss of vascular reactivity, Restoring CVR in CAA